Search and Rescue: Development and Verification of a Modernized Passive Floating System for Payload Sea Recovery - Göser, Johannes; Drescher, Oliver; Hörschgen-Eggers, Marcus; Gemeinhardt, Ulf (2019)
For most suborbital space flights, the successful recovery of the experimental payload is a critical point at the very end of the mission. Beside land based recovery, particular missions require a sea recovery in the Arctic Ocean. Therefore, a variety of passive floating systems have been developed and used by DLR's Mobile Rocket Base (MORABA). Using the vast experience of multiple successful sea recoveries over the last decades, some of the latest development work has been dedicated to a modernised version. In cooperation with TEXCON GmbH, improved Long-term floating behaviour and a considerably reduced packing volume have been achieved by using innovative materials and manufacturing technologies. Prior to the first successful operation of the improved passive floating system, various tests had to be performed to verify the floater's functionality and durability. In this context, the Neutral Buoyancy Facility's (NBF) diving pool of ESA's European Astronaut Centre (EAC) in Cologne was offered for investigating different recovery scenarios. This paper describes the development and verification process of the modernized passive floating system. Furthermore, results of the first successful operation during the PMWE mission are presented.